2014
DOI: 10.1177/1556264614540591
|View full text |Cite
|
Sign up to set email alerts
|

Parent Ratings of Ability to Consent for Clinical Trials in Fragile X Syndrome

Abstract: Advances in understanding neurobiology and intellectual disabilities have led to clinical trials testing new medications. This study assessed parents’ perceptions of the ability of their son or daughter with fragile X syndrome (FXS), an inherited form of intellectual disability, to participate in the consent process for clinical trials. Four hundred and twenty-two families participated in a survey that included six items assessing various aspects of the ability to provide consent. A rank ordering of decisional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Identifying new mechanisms to improve research participant comprehension during the process is necessary to promote the ethical conduct of research. However, along with other research evidence, this study demonstrates that different formats of informed consent may not be applicable to all research contexts (Bailey et al, 2014). For example, in this study, we found that for 6 of the 14 items on the survey, participants in the simplified paper-based consent group had higher mean scores than those in the electronic informed consent group.…”
Section: Discussionmentioning
confidence: 56%
“…Identifying new mechanisms to improve research participant comprehension during the process is necessary to promote the ethical conduct of research. However, along with other research evidence, this study demonstrates that different formats of informed consent may not be applicable to all research contexts (Bailey et al, 2014). For example, in this study, we found that for 6 of the 14 items on the survey, participants in the simplified paper-based consent group had higher mean scores than those in the electronic informed consent group.…”
Section: Discussionmentioning
confidence: 56%
“…Males diagnosed with FXS typically have impairment ranging from mild to severe; females are generally less impaired [12]. This wide range of cognitive skills among those with FXS can result in variable decisional capacity and the ability to make choices [13].…”
Section: Overview Of Fragile X Syndromementioning
confidence: 99%
“…To date, most research on individuals with FXS has been noninvasive, limited to parent surveys and secondary assessment of clinical data [13,14]. Studies such as these typically involve straightforward consent/assent processes or parental consent.…”
Section: Overview Of Fragile X Syndromementioning
confidence: 99%
See 2 more Smart Citations